2006
DOI: 10.1055/s-2006-951527
|View full text |Cite
|
Sign up to set email alerts
|

Interplays between Reactions within and without the Catalytic Cycle of the Heck Reaction as a Clue to the Optimization of the Synthetic Protocol

Abstract: This account presents previous and recent mechanistic studies of the Heck reactions reported by the authors whose attention has been focused on a problem of the coupling of catalyst transformations within and without the catalytic cycle. Based on the understanding of the interaction mechanism between these processes a development of new methods of Heck chemistry became conceivable. In particular, such a rational approach allowed an elaboration of the ligand-free systems, which are effective not only in the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 104 publications
3
74
0
2
Order By: Relevance
“…[93,94] It is highly probable that in these cases the Heck coupling reaction proceeds through the oxidative addition of the aryl halide on the nanoparticles surface, and the oxidized Pd species thus formed are detached from the surface and enter into the main catalytic cycle. [95] The Pd 0 formed in the main catalytic cycle, after bhydride and reductive elimination steps, can either continue in the catalytic cycle or fall back to the nanoparticle reservoir. [67] The same behavior was observed in the hydroformylation of olefins catalyzed by Rh 0 nanoparticles prepared in BMI·PF 6 .…”
Section: Catalytic Reactionsmentioning
confidence: 99%
“…[93,94] It is highly probable that in these cases the Heck coupling reaction proceeds through the oxidative addition of the aryl halide on the nanoparticles surface, and the oxidized Pd species thus formed are detached from the surface and enter into the main catalytic cycle. [95] The Pd 0 formed in the main catalytic cycle, after bhydride and reductive elimination steps, can either continue in the catalytic cycle or fall back to the nanoparticle reservoir. [67] The same behavior was observed in the hydroformylation of olefins catalyzed by Rh 0 nanoparticles prepared in BMI·PF 6 .…”
Section: Catalytic Reactionsmentioning
confidence: 99%
“…All of these species enter (and are interconverted by) the catalytic cycle. [16][17][18] However, the coupling activity is expected to decrease with the size of the Pd aggregates. Finally, the irreversible precipitation of Pd black will occur, shifting the equilibria b towards inactive species, and stalling catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] Typical means to prevent this deactivation are the addition of stabilizers (often in excess) for Pd(0), such as phosphane and carbene ligands. Other additives or solvents have been used to stabilize the Pd particles.…”
Section: Introductionmentioning
confidence: 99%
“…A simple Heck reaction [12][13][14][15] of iodobenzene and methyl acrylate has been selected as a test reaction. Recently it was indicated that the pressurization with CO 2 accelerated the rate of Heck reactions with a Pd-TPP (TPP: triphenylphosphine) complex catalyst for a few selected substrates although the reactions took place in homogeneous liquid phases and CO 2 was not a reactant [16].…”
Section: Methodsmentioning
confidence: 99%